2011
DOI: 10.1111/j.1460-9568.2011.07901.x
|View full text |Cite
|
Sign up to set email alerts
|

Gap junction‐mediated calcium waves define communication networks among murine postnatal neural progenitor cells

Abstract: In the postnatal neurogenic niche, two populations of astrocyte-like cells (B cells) persist, one acting as neural progenitor cells (NPCs, B1 cells) and one forming a structural boundary between the neurogenic niche and the striatum (B2 cells, niche astrocytes). Despite being viewed as two distinct entities, we found that B1 and B2 cells express the gap junction protein connexin 43 and display functional coupling involving 50-60 cells. Using neonatal electroporation to label slowly cycling radial glia-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 25 publications
5
97
0
Order By: Relevance
“…Gap junctions appear to function via several mechanisms in Ca 2+ wave propagation. In one mechanism, gap junctions act intercellularly to propagate Ca 2+ waves by allowing the spread of Ca 2+ releasing factors, including Ca 2+ itself (Leybaert et al, 1998;Isakson et al, 2006;Lacar et al, 2011). A second mechanism has been described in the developing mammalian CNS and involves extracellular propagation via ATP released from hemichannels acting via P2 receptors to trigger Ca 2+ waves (Dale, 2008;Orellana et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gap junctions appear to function via several mechanisms in Ca 2+ wave propagation. In one mechanism, gap junctions act intercellularly to propagate Ca 2+ waves by allowing the spread of Ca 2+ releasing factors, including Ca 2+ itself (Leybaert et al, 1998;Isakson et al, 2006;Lacar et al, 2011). A second mechanism has been described in the developing mammalian CNS and involves extracellular propagation via ATP released from hemichannels acting via P2 receptors to trigger Ca 2+ waves (Dale, 2008;Orellana et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Connexins are known to mediate Ca 2+ waves in mammalian cells (Toyofuku et al, 1998;Lacar et al, 2011;Orellana et al, 2012), although a role in vertebrate neural plate induction has not been demonstrated. Gap junctions appear to function via several mechanisms in Ca 2+ wave propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, connexin 43 was shown to prevent HSC senescence by transferring reactive oxygen species into the supporting stromal cells, thus reducing their damage to HSCs (Taniguchi Ishikawa et al, 2012). In the mouse subventricular NSC niche, the gap junction-mediated calcium transfer between supporting astrocytes and NSCs is important for NSC proliferation (Lacar et al, 2011). In Drosophila ovary and testis, Zero population growth (Zpg), a gap junction protein, is required for GSC maintenance and differentiation (Gilboa et al, 2003;Tazuke et al, 2002).…”
Section: Other Classes Of Adhesion Moleculesmentioning
confidence: 99%
“…Further, engagements with the vasculature were also detected in vascular regions devoid of mural cell coverage, indicating direct contacts (Tavazoie et al, 2008). Type B1 stem cells were found to extend long cytoplasmic processes with their endfeets contacting nearby striatal vessels (Lacar et al, 2011;Mirzadeh et al, 2008) and see Fig. 1A.…”
Section: The Svz Vascular Nichementioning
confidence: 92%
“…Does the apparent communication between NSCs and neural progenitors with blood vessels also involve a reciprocal response of NSCs affecting blood vessel characteristics? Type B1 cells were indeed found capable of transmitting Ca ++ currents to capillaries through their cytoplasmic processes using via gap junctions (Lacar et al, 2011) and purinergic signaling from B1 cells to pericytes evoked local vasoconstriction (Lacar et al, 2012b). Induction of NSC activation by intra-ventricular injection of EGF and bFGF resulted in an opposing vascular response of vasorelaxation and increased blood flow.…”
Section: The Svz Vascular Nichementioning
confidence: 98%